PERANAN ROOM ATTENDANT DALAM MENANGANI HYGIENE DAN SANITASI KAMAR DI OS HOTEL BATU AJI BATAM - Hot Bonar Ampuan Sinaga; Nensi Lapotulo (JURNAL MEKAR, 2022)
The cleanliness factor in the hotel is closely related to cleanliness and sanitation. This affects the quality and comfort in the service of Hotel and becomes an attraction for guests/consumers to come and use hotel services. However, it is not uncommon for problems in the implementation of hygiene and sanitation to arise due to the implementation of SOP (Company Operational Standards) to maintain the cleanliness of the room which has not been implemented properly and regularly. This study is a descriptive qualitative research that aims to determine determine the duties of the room attendant in maintaining the cleanliness and sanitation of the rooms and to find out how the room attendants maintain the cleanliness and sanitation of hotel rooms. The object of this research is the room attendant at the OS Hotel Batu Aji Batam. The participants in this study were the Housekeeping Department. With the validity of the data, namely using Source Triangulation. The results showed that the application of hygiene and sanitation carried out by OS Hotel Batu Aji Batam is carried out in accordance with the provisions of the SOP that have been set. In this case, all room staff are required to always apply and pay attention to hygiene and sanitation in carrying out their duties and responsibilities. In addition, room attendants are also required to check and coordinate regularly in carrying out hotel service tasks. Thus, the application of hygiene and sanitation in Orange Sky Batam Hotel rooms can be carried out optimally and regularly